2016
DOI: 10.3390/ijerph13111153
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Serum Bisphenol A with Thyroid Autoimmunity

Abstract: Introduction: Data on the association of bisphenol A (BPA) exposure and autoimmunity in humans is unclear. Objective: To elucidate the influence of BPA on thyroid autoimmunity, in the present study we assessed the association between serum BPA and thyroid autoantibodies. Methods: Serum samples from 2361 subjects, aged ≥15 years, from the Thai 4th National Health Examination Survey were measured for BPA, antithyroglobulin (TgAb), antithyroperoxidase (TPOAb) and antithyrotrophin receptor (TRAb) antibodies. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 31 publications
0
16
1
1
Order By: Relevance
“…Similar results for phthalates were found in the Korean National Environmental Health Survey (KoNEHS) 2012-2014, but BPA presented a negative association with TSH (Park et al 2017). However, in a similar health cross-sectional study in Thailand, the Thai National Health Examination Survey IV 2009, a negative correlation between BPA and free T4 was detected in males, without changes in TSH levels (Sriphrapradang et al 2013), and in this same group, BPA was also associated with thyroid autoimmunity, with an increase in TPO antibody positivity (Chailurkit et al 2016). The Taiwan Environmental Survey for Toxicants (TEST) 2013 showed negative associations between free and total T4 levels and some phthalate metabolites in adults; however, a positive association with free T4 levels was found in children (Huang et al 2017a,b).…”
Section: Plasticizersmentioning
confidence: 85%
“…Similar results for phthalates were found in the Korean National Environmental Health Survey (KoNEHS) 2012-2014, but BPA presented a negative association with TSH (Park et al 2017). However, in a similar health cross-sectional study in Thailand, the Thai National Health Examination Survey IV 2009, a negative correlation between BPA and free T4 was detected in males, without changes in TSH levels (Sriphrapradang et al 2013), and in this same group, BPA was also associated with thyroid autoimmunity, with an increase in TPO antibody positivity (Chailurkit et al 2016). The Taiwan Environmental Survey for Toxicants (TEST) 2013 showed negative associations between free and total T4 levels and some phthalate metabolites in adults; however, a positive association with free T4 levels was found in children (Huang et al 2017a,b).…”
Section: Plasticizersmentioning
confidence: 85%
“…This group mainly included the interference of BPA on thyroid hormones, [ 7 ] exposure of BPA and potential risks in infants, children and pregnant women, [ 42 ] and the association of BPA with thyroid disease. [ 43 ] The group 2 (green) mainly referred the mechanism of BPA's effect on thyroid hormones. [ 35 ] The group 3 (purple) contained 44 records and the first article was published in 2005.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of BPA on thyroid autoimmunity is controversial (Table 4). Whereas urinary BPA concentration was associated with variations of TH levels both in children and adults of both sexes, independent of serum thyroglobulin antibodies (TgAb) and thyroid peroxidase antibodies (TPOAb) [149,155], another study found a positive relationship between serum BPA and TPOAb in men and women [156]. Moreover, a significant negative correlation of serum BPA with FT4 in male subjects was found only after exclusion of subjects with positive thyroid antibodies, suggesting that TgAb might be a mediator of the relationship between BPA and FT4 [144].…”
Section: Association With Thyroid Diseasesmentioning
confidence: 93%